Symbiosis of Email and SMS - Arman H. Harutyunyan; Gharagyozyan, Sona H. (Изд-во НАН РА)
The specific features of the means of written communication through computer and mobile networks, as well as the prehistory of the establishment of hybrid communication system using IP and GSM network technologies have been examined.
Keywords: Mathematics; Computer software